Robot-Assisted Excision of a Pararectal Gastrointestinal Stromal Tumor in a Patient with Previous Ileal Neobladder - A. Ploumidis; A. Mottrie; A. F. Spinoit; M. Gan; V. Ficarra; R. Andrianne (Case Reports in Urology)
Gastrointestinal stromal tumors (GISTs) are the most frequent mesenchymal tumors of the gastrointestinal tract with surgical resection remaining the cornerstone of therapy. Pararectal lesions are considered to be technically difficult and pose in some cases a challenge. We report, to the best of our knowledge, the first robotic-assisted pararectal GIST excision. A 43-year-old man was referred to our center with pararectal GIST recurrence, despite treatment with targeted therapy. Eleven years ago, he underwent extensive abdominal surgery including cystoprostatectomy with ileal neobladder diversion due to GIST resection in the rectoprostatic space. Robot-assisted surgical resection was successfully performed without the need for temporary colostomy. The postoperative course of the patient was uneventful, and the pathology report confirmed a GIST recurrence with negative surgical margins and pelvic lymph nodes free of any tumor. Robotic-assisted pelvic surgery can be extended to incorporate excision of pararectal GISTs, as a safe, less invasive surgical alternative with promising oncological results and minimal injury to adjacent structures.